2013
DOI: 10.4103/0970-9290.123362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accuracy of portable fingertip pulse oximeter, as compared to that of a hospital oximeter with digital sensor

Abstract: According to the methodology of the research, the PPO has similar accuracy to the conventional hospital oximeter with digital sensor. The PPO can be used in dental treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…A study involving 55 dental patients in Brazil found no statistically significant difference between a portable fingertip oximeter and hospital pulse oximeters. [29] The non-invasive SpO 2 of each device was measured by simultaneous application of the fingertip probe at six time intervals during the dental procedures. Although this study was conducted in a clinical setting, it included insufficient comparisons for a Bland-Altman analysis, and the Pearson correlation coefficient reported is not an appropriate method for equipment comparison.…”
Section: Clinical Trialmentioning
confidence: 99%
“…A study involving 55 dental patients in Brazil found no statistically significant difference between a portable fingertip oximeter and hospital pulse oximeters. [29] The non-invasive SpO 2 of each device was measured by simultaneous application of the fingertip probe at six time intervals during the dental procedures. Although this study was conducted in a clinical setting, it included insufficient comparisons for a Bland-Altman analysis, and the Pearson correlation coefficient reported is not an appropriate method for equipment comparison.…”
Section: Clinical Trialmentioning
confidence: 99%
“…Numerosos autores se han planteado la duda acerca de la eficacia de los diferentes oxímetros del mercado, muchos de los cuales encuentran gran proximidad entre los datos de los dispositivos testeados, donde los valores mínimos y máximos en ocasiones no coinciden, pero mostrando diferencias menores al 3% y sin diferencias estadísticamente significativas 12,13 . Utilizando el método de Bland-Altman para comparar ambos dispositivos, se verificó la proximidad de cero en los valores encontrados.…”
Section: Discussionunclassified
“…An advantage over venous blood and other body components including bone, tissue, skin, muscle, and fat is that arterial blood is the only one that absorbs light due to its pulsating movement over time. (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…According to various studies, youngsters in developed nations are increasingly aware of the need for dental care, and more people are seeking out procedures to improve their oral health. (9,10). Dental surgical procedures can take a while and involve the use of local anaesthetics, which can cause anxiety and behavioural problems.…”
Section: Introductionmentioning
confidence: 99%